Ketone Bodies in the Brain Beyond Fuel Metabolism: From Excitability to Gene Expression and Cell Signaling - García-Rodríguez, Darío; Giménez-Cassina, Alfredo (Frontiers in Molecular Neuroscience, 2021)
Ketone bodies are metabolites that replace glucose as the main fuel of the brain in situations of glucose scarcity, including prolonged fasting, extenuating exercise, or pathological conditions such as diabetes. Beyond their role as an alternative fuel for the brain, the impact of ketone bodies on neuronal physiology has been highlighted by the use of the so-called “ketogenic diets,” which were proposed about a century ago to treat infantile seizures. These diets mimic fasting by reducing drastically the intake of carbohydrates and proteins and replacing them with fat, thus promoting ketogenesis. The fact that ketogenic diets have such a profound effect on epileptic seizures points to complex biological effects of ketone bodies in addition to their role as a source of ATP. In this review, we specifically focus on the ability of ketone bodies to regulate neuronal excitability and their effects on gene expression to respond to oxidative stress. Finally, we also discuss their capacity as signaling molecules in brain cells.